2020
DOI: 10.1186/s12967-020-02412-x
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a prognostic model of resectable small-cell lung cancer: a large population-based cohort study and external validation

Abstract: Background: Survival outcomes of patients with resected SCLC differ widely. The aim of our study was to build a model for individualized risk assessment and accurate prediction of overall survival (OS) in resectable SCLC patients. Methods: We collected 1052 patients with resected SCLC from the Surveillance, Epidemiology, and End Results (SEER) database. Independent prognostic factors were selected by COX regression analyses, based on which a nomogram was constructed by R code. External validation were performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 28 publications
3
27
1
Order By: Relevance
“…An etoposide and cisplatin regimen with concurrent radiation is recommended as standard treatment for LD-SCLC and was shown to enhance survival and was well tolerated [ 23 , 35 37 ]. Although chemotherapy was associated with longer survival in our analysis, the impact was not statistically significant, which is contrary to previous reports [ 25 , 38 ]. This may be due to relatively small number of patients who did not receive chemotherapy.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…An etoposide and cisplatin regimen with concurrent radiation is recommended as standard treatment for LD-SCLC and was shown to enhance survival and was well tolerated [ 23 , 35 37 ]. Although chemotherapy was associated with longer survival in our analysis, the impact was not statistically significant, which is contrary to previous reports [ 25 , 38 ]. This may be due to relatively small number of patients who did not receive chemotherapy.…”
Section: Discussioncontrasting
confidence: 99%
“…This may be due to the smaller tumor size in sublobectomy compared to lobectomy and pneumonectomy (median, 18 vs. 27.5 vs. 42 mm; p < 0.001). Lymph node status is closely related to surgical outcome, and several studies have also shown that lymph node metastasis predicts surgical outcome in SCLC [ 5 , 38 ]. Thus, mediastinal lymph node dissection should be performed in surgical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the effects of additional tumor factors have not been taken into account [ 10 ]. Nomogram, as a practical application tool, makes an individual prediction by quantifying risk factors into scores and shows more accurate and useful than the AJCC-TNM staging system in a variety of cancers [ 11 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the effects of additional tumor factors have not been taken into account [10]. Nomogram, as a practical application tool, makes an [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Of these, only manuscrpits dealing directly with surgical pulmonary resection in SCLC were selected. Based on these criteria, 14 publications were identified and included in the review [8][9][10][11][12][13][14][15][16][17][18][19][20][21](Tab. 1).…”
Section: Review Methodsmentioning
confidence: 99%